Efecto de Trichoderma spp. y Bacillus spp. en el rendimiento productivo del cultivo de fríjol caupí (Vigna unguiculata L. Walp) - Santana Carrasco, Bryan Steven (2023)
The purpose of the research was to evaluate the effect of Trichoderma and Bacillus to promote the productive yield of the cowpea bean crop by applying them every 8 and 15 days and their interaction. The evaluated treatments were: Trichoderma + 0.5 g/L water (T1), Trichoderma + 0.5 g/L water (T2), Bacillus + 0.5 ml/L water (T3), Bacillus + 0.5 ml/L water (T4), Bacillus x Trichoderma + 1 ml/L water (T5), Bacillus x Trichoderma + 1 ml/L water (T6). The recorded variables were: Pod length (cm), Number of pods per plant, Weight of 100 green beans (g), Number of green beans per pod, Yield of green bundles per hectare (Kg). Data analysis was performed using descriptive statistics, analysis of variance (ANOVA), and the separation of means with Tukey's test at 5% probability of error. The analysis of variance showed that the biostimulants promoted the development of pod length, number of pods, pod weight and yield; the application frequencies of the evaluated biostimulants did not influence the yield of the cowpea bean crop.